استخدام النسب المالية في تقييم الأداء المالي للمؤسسات الاقتصادية الجزائرية دراسة حالة المؤسسة الوطنية لخدمات الآبار خلال الفترة الممتدة ما بين 2012-2021 - مسعي محمد عبد المالك; بوجمعة ياسين; بلة باسي فارس (جامعة الوادي University of Eloued, 2024)
دفت هذه الدراسة الى التعرف على فعالية استخدام النسب المالية في تقييم الأداء المالي للمؤسسات الاقتصادية الجزائرية دراسة حالة المؤسسة الوطنية لخدمات الآبار وذلك خلال الفترة 2012-2021 حيث تم استخدام منهج دراسة الحالة كما تم استخدام بعض النسب المالية منها نسب السيولة و نسب النشاط ونسب الربحية ونسب الهيكل المالي بالإضافة الى مؤشرات التوازن المالي ومن النتائج التي تم التوصل اليها ان مؤسسة خدمات الآبار وضعها المالي جيد وغير معرضة الى مخاطر الفشل المالي . This study aimed to identify the effectiveness of using financial ratios in evaluating the financial performance of Algerian economic institutions. A case study of the National Well Services Corporation during the period 2012-2021, where the case study approach was used. Some financial ratios were also used, including liquidity ratios, activity ratios, profitability ratios, and ratios. The financial structure, in addition to the financial balance indicators, and the results reached are that the Well Services Corporation has a good financial position and is not exposed to the risks of financial failure.
The use of financial ratios in evaluating the financial performance of Algerian economic institutions. A case study of the National Well Services Corporation during the period 2012-2021
Keywords: تقييم الأداء المالي; الربحية; النشاط; الهيكل المالي; التوازن المالي; Evaluating financial performance; liquidity; profitability; activity; financial structure; and financial balance